Cancer Associated Fibroblasts (CAFS) and their Indispensable Role in Tumor Microenvironment: An Update - Shubhangi Pareek1 , Swagatika Panda2 , Neeta Mohanty3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Cancer-associated fibroblasts commonly known as CAFs which have a modified phenotype as comparedto normal fibroblasts are exclusively present in the tumor microenvironment surrounding the tumor mass.They play inevitable roles in tumor initiation, progression, invasion, and metastasis. The constant crosstalk present in between the cancer cells and CAFs is responsible for the maintenance of such a malignantenvironment. Thus,they may prove to be efficient targets in the field of cancer therapeutics which may yieldexcellent results. This review throws light upon their much evident roles in carcinogenesis as well as howthe mechanisms driven by them may be targeted in therapeutic interventions.